PRICING SINGLE AND DOUBLE ASSET BARRIER OPTION USING REFLECTION PRINCIPLE - AL KAHFI (NIM: 10114032), MUHAMMAD
One of the well-known derivative instruments is option. More research on option has been made in recent years to improve the results of Black-Scholes in obtaining the vanilla option price (Ã‚Â± 40 years ago). One of exotic option that is quite famous is barrier option, i.e. the option that its payoff depends on whether the asset (in this case stock) ever Ã‚Â”touchÃ‚Â” a barrier or not. Barrier options are often preferred over vanilla option due to the lower price. Barrier option price calculation can be done analytically or numerically. The method that we use in this final project is done analytically by using the reflection principle. Then we compare to the result of numerical calculations using the Monte Carlo method. The principle of the barrier option on 1 asset is then be developed into double assets barrier option, i.e. barrier option whose underlying asset consists of 2 assets. The calculation of barrier option of double assets is also carried out in this final project on the condition that the correlation of both assets can be expressed as Ã‚Â±cos⁡(π/n) for a natural number n. At the end, the analysis of the investment strategy is done using the barrier option which is then compared to the investment strategy using the butterfly spread.